STRATEGI PULL AND PASS DIVISI KOMUNIKASI DAN MARKETING JAKARTA SMART CITY PADA APLIKASI JAKARTA KINI (JAKI) - Farahdinta Destanti, (2021)
The advancement of technology now cannot be separated from human life because of its impact that makes easier for activites such as easy access to information from a media. The use of this media is not only used by individuals, but also by institutions such as Jakarta Smart City. Jakarta Smart City comes with an application called JAKI (Jakarta Kini) with various features insides which are present with the aim of facilitating the lives of people who live or have activities in Jakarta. As an application that is being introduced to the public, Jakarta Smart City, especially in the communication and marketing division whom implements two marketing public relations concepts, there are pull strategy and pass strategy. The purpose of this study is to analyzed the marketing public relations strategy which carried out by the communication and marketing division by implementing the pull and pass strategy for the JAKI application. This research uses The Whalen 7 Steps Strategic as the theory and used qualitative approach with a case study method. The the data collection technique is done through interviews and documentation. The results show that the pull and pass strategies that implemented into JAKI are the creation of contents on social media, press releases, involvement of community leaders, email blasts, online events, and exhibitions. There were obstacles from activities carried out due to the existence of the pandemic, such as the difficulty of coordinating with the division team, intergovernment and obtaining permission to produce content in the field.